Firm Entry and Exit in the Canadian Manufacturing Sector - John R. Baldwin; Paul K. Gorecki (Queen's University, Department of Economics, 1990)
While the entry and exit of firms is an important component of many economic models, measures of the importance of the associated firm turnover have been lacking. Using a specially constructed data base from the Canadian Census of Manufactures that allows firms and establishments to be followed over time. this paper presents basic data on the importance of entry and exit. It discuss the conceptual, theoretical, and empirical issues involved in measuring entry and exit and in building a longitudinal data set for this purpose. It then presents measures of entry and exit in the 1970s and 1980s. In doing so, it focuses both on the size of entrants at birth and also on their cumulative effect. It describes the transition path on entrants as they move from a stage of infancy to early adolescence. This is done by presenting the exit rates of births, their length of life and the growth path of entrants. In each case, the paper takes care to measure two different types of entry and exit and to compare the performance of each. In particular, entry by acquisition and exit by divestiture are compared to entry by plant opening and exit by plant closing. The paper shows that while entrants are small at birth, the cumulative effect of successive cohorts of new firms adds up to a significant fraction of all firms and of total sales by the end of a decade.
Keywords: 330